Regulatory intermediaries and the challenge of democratic policing - Cheng, Tony (Criminology & public policy, 2022)
This study examines a model for achieving democratic governance over police departments: regulatory intermediaries, where non-state actors are empowered with regulatory authority over public institutions. Drawing on a decade of transcripts from monthly public meetings held by the Chicago Police Board (September 2009–February 2021), this study finds, however, that regulatory intermediaries can regulate the public as much as it does the public institution. We identify three ways that the regulating public becomes the regulatory target: through (1) institutional rules, (2) hierarchized responses, and (3) norms of civility.